"The drug issue really isn't the main problem"— A photovoice study on community perceptions of place, health, and substance abuse. (May 2019) - D'Angelo, Karen A.; Her, Wonbin
Abstract: Substance abuse is a complex and challenging public health problem. In order to better address substance abuse, it is vital to understand the perspectives of people whose communities are disproportionately impacted by it. This photovoice study aimed to understand how community members perceive the relationship between place, health, and substance abuse in Hartford, Connecticut, one city grappling with substance abuse and its related challenges. Findings revealed three themes: perceived place-based environmental risk factors for substance abuse; coping strategies to maintain sobriety in this challenging environmental context; and participants' recommendations for addressing substance abuse. Implications are discussed. Highlights: Substance abuse identified as a major health-related theme in photovoice study. Evidence of pervasive substance abuse was well-illustrated in quotes and pictures. Participants identified perceived place-based environmental risk factors. Participants shared strategies for managing such risks to maintain sobriety. Participants made recommendations for preventing and treating substance abuse.